Load condition of the wrist during the forward handspring, the forward handspring with ulnar deviated hand positioning and the backward handspring - Angst, M.; Lorenzetti, S.; Schellenberg, F.; List, R. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this research was to deterime the loading conditions throughout the forward handspring, the forward handspring with ulnar deviated hand positioning and the backward handspring using an inverse dynamics approach based on simultaneously acquired kinetic and kinematic data. 14 gymnasts performed five of each movement. The range of motion (ROM) around the pronation/supination axis in the forward handspring with ulnar deviated hands was significantly higher than in the two other executions. The calculated moment acting on the wrist during backward handsprings exceeded the ones during the forward executions significantly. Due to the knowledge of the loading conditions, long-term damages can be estimated and minimized in such repetitively excessive motions.